PENERAPAN PELAYANAN PAJAK KENDARAAN BERMOTOR RODA DUA DI SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) KOTA MAKASSAR - Ikmawati, Ikmawati; Mahsyar, Abdul; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to describe and explain the Application of motorcycle Tax Services in the One-Stop One-Stop Administration (Samsat) Makassar City. This study used a qualitative descriptive method by conducting data collection techniques through observation and interviews. The data obtained from the results of this study were reviewed using data reduction techniques, data presentation and conclusion. completion, Service Fees, Service Products, Providing Facilities and Infrastructure and Competence of Service Officers. In the application of the services provided by the Makassar City Samsat, it provided public services in accordance with the Operational Standards set by the Makassar City Samsat so as to provide the best service to the taxpayer community.